Seasonal variations of the Cladocerans in the Shatt Al-Arab River, Southern Iraq - Ajeel, Shaker G.; Abbas, Mohammed F. (Iraqi Journal of Aquaculture, 2016)
Samples were collected seasonally from three stations (Al-Ashar, Abu Al-Khasib and Al-Faw) in the Shatt Al-Arab River by a plankton net (85 μm mesh-size and 40 cm mouth aperture), from January to November 2013. Some physical and chemical parameters of the water were monitored such as, water temperature, salinity, pH, dissolved oxygen, Total Dissolved Solids (TDS) and turbidity. The density of Cladocera ranged between 0.0 ind/m3 during spring and summer at Al-Faw station to 18922 ind/m3 during summer at Al-Ashar station. Five, two and one species of Cladocera were recorded at the three stations, respectively. Moina affinis and Diaphanosoma brachyurum were the dominant species at study area. Maximum diversity index (H) (0.7) was obtained at stations 1 and 2 during winter and spring respectively and higher evenness value (J) (0.4) was recorded at station 1 and 2 during winter, while higher richness (D) (6.1) was obtained at station 1 during winter and lowest value (0.0) at station 3. Jaccard׳s index revealed higher similarity between stations 1 & 2 and lower values between station 1 and 3.